The Philosophy Of Theology: The Existence of God in Human’s Life - Ahida, Ridha (International Journal of Psychosocial Rehabilitation, 2020)
This research discusses the Philosophy of Theology used to uncover the existence of God in human’s life. The object of the research are basically the perceptions of the ancients Greece, Christians and Muslims philosophers on the existence of God in human’s life. The research employs divinity philosophical approach to uncover how the ancients Greece, Christians and Muslims philosophers perceive the existence of God in human’s life. Divinity philosophical approach is used to describe the existence of God in human’s life and the relationship between mankind and God according to the ancients Greece, Christians and Muslims philosophers. The findings revealed that the discussions about the existence of God by the philosophers have been around since 600 BC. Some of the most intersecting topics on divinity among philosophers are; the existence of God; the creation of the entire world and mankind; the position of God after the creation; what and who God(s) are; proofs that God exists, and the relationship between faith and ratio. Implicitly, the first seed on problem related to divinity were found on the early statements of philosophers related to the “arche” “prime matter” of the universe. The existence of God was not supposed to be literally and dogmatically accepted, it was supposed to be given a rational explanation. The understanding of the existence of God cannot be separated from the widely accepted views of the philosophers at certain time. Innovation and the emergence of originality of ideas related to the concept of divinity from the philosophers have also said to be play an important role on influencing how community perceive the existence of God during the life period of the philosophers and after it.